The professional identity statuses of boys and girls with different socialization conditions in the focus of value, regulatory and temporal determinants - Ralnikova, I.A. (Socialʹnaâ Psihologiâ i Obŝestvo, 2025)
Context and relevance. The formation of the professional identity of boys and girls who socialize in the family and outside the family is a significant scientific problem. Psychological research covers the value bases of professional self-determination, self-regulation processes, and ideas about the professional future. At the same time, these aspects are considered in isolation from each other, and the conditions of socialization are not always taken into account. Objective. To identify differences in values, regulatory processes, and emotional assessment of the image of a professional future, and to determine predictors of the professional identity statuses of boys and girls from blood families and pupils of care centers for children left without parental care. Hypotheses. Boys and girls who socialize in families and child care centers have differences in attitude: 1) quantitative and meaningful characteristics of predictors of professional identity statuses (basic); 2) values, self-regulation, emotional attitude to the image of the professional future (additional). Methods and materials. The study involved 260 respondents aged 15-17 years (52% of boys, 48% of girls), 140 from blood families, 120 from child care centers. The following questionnaires were used: "Methodology for studying professional identity statuses" (A.A. Azbel, A.G. Gretsov), "Morphological test of life values" (V.F. Sopov, L.V. Karpushina), questionnaire "Style of self-regulation of behavior" (V.I. Morosanova), method "Semantic time differential" (L.I. Wasserman, E.A. Trifonova, K.R. Chervinskaya). Results. Young men and women from blood-related families have a crisis of choice status, while students at care centers have a status of uncertain professional identity. In the context of family socialization, compared with non-family, spiritual, moral and pragmatic values are more significant, self-regulation is more developed, and the image of the future is more positive. Conclusions. The conditions of socialization of boys and girls in the family and outside the family determine differences in predictors of the formation of professional identity statuses. Контекст и актуальность. Становление профессиональной идентичности юношей и девушек, социализирующихся в семье и вне семьи, выступает в качестве значимой научной проблемы. Психологические исследования охватывают ценностные основы профессионального самоопределения, процессы саморегуляции, представления о профессиональном будущем. При этом указанные аспекты рассматриваются изолированно друг от друга, не всегда учитываются условия социализации. Цель. Выявить различия в ценностях, регуляторных процессах, эмоциональной оценке образа профессионального будущего, определить предикторы статусов профессиональной идентичности юношей и девушек из кровных семей и воспитанников центров помощи детям, оставшимся без попечения родителей. Гипотезы. Юноши и девушки, социализирующиеся в семьях и центрах помощи детям, имеют различия в отношении: 1) количественных и содержательных характеристик предикторов статусов профессиональной идентичности (основная); 2) ценностей, саморегуляции, эмоционального отношения к образу профессионального будущего (дополнительная). Методы и материалы. В исследовании приняли участие 260 респондентов в возрасте 15-17 лет (52% - юноши, 48% - девушки), 140 из кровных семей, 120 из центров помощи детям. Использовались опросники: «Методика изучения статусов профессиональной идентичности» (А.А. Азбель, А.Г. Грецов), «Морфологический тест жизненных ценностей» (В.Ф. Сопов, Л.В. Карпушина), опросник «Стиль саморегуляции поведения» (В.И. Моросанова), методика «Семантический дифференциал времени» (Л.И. Вассерман, Е.А. Трифонова, К.Р. Червинская). Результаты. У юношей и девушек из кровных семей преобладает статус «кризис выбора», у воспитанников центров помощи - статус неопределенной профессиональной идентичности. В условиях семейной социализации, по сравнению с внесемейной, духовно-нравственные и прагматические ценности более значимы, сильнее развита саморегуляция, образ будущего более позитивный. Выводы. Условия социализации юношей и девушек в семье и вне семьи обусловливают различия в предикторах формирования статусов профессиональной идентичности.